Prevalence of Hepatitis A, B and C Virus Infection in the Municipality of Maringá, Northwestern Region of the State of Paraná, From 2001 to 2004 - Babinski, Celiel Elezi (2008)
All types of viral hepatitis are a public health concern worldwide. Disease is caused by viruses identified by the letters of the alphabet, such as Hepatitis A, B, C, D, E and G. The prevalence of Hepatitis A, B and C in the municipality of Maringá PR Brazil has been evaluated between 2001 and 2004, within the epidemiological context of age bracket and sex. Bibliographical surveys have been undertaken by comparisons and by consulting the Regional Health Unit and the Brazilian System of Disease Notification (Sinan). Whereas highest prevalence of Hepatitis A occurred in males within the 1-14 year bracket; highest prevalence of Hepatitis B and C occurred in males within the 20-49 year bracket. A significant increase in Hepatitis C occurred in 2003 and 2004.